Handling information: Matching input-algorithms to output-algorithms in observational notational analysis systems - Verlinden, M. (International Journal of Computer Science in Sport, 2002)
"Information", which is embodied by analysed data - gathered and processed by notation systems for sports applications (feedback, technique and tactics analysis) - can be defined in a broad sense as "that what deprives the already known information with uncertainty or the unknown of the user, at the moment of reception of the message" (e.g. trainer, player, coach, scientist). It is necessary to take into account both an information source, which delivers a message, and a user of that information, in order to consider the concept of information. Notation systems do have - due to this definition of "information" (earlier described by Shannon and Hartley, 1948) - a duality in their conceptual reason of existence: